NuSTAR Analysis of the 2024 Periastron Passage of TeV Binary PSR B1259-63 - Oliver J. Roberts; Philip Kaaret; M. Lynne Saade; Chien-Ting Chen; Steven R. Ehlert; Ioannis Liodakis; Martin C. Weisskopf (The Astrophysical Journal, 2025)
PSR B1259-63 is a well-studied TeV binary, with an energetic pulsar in orbit around a Be star. Using Nuclear Spectroscopic Telescope Array observations during the 2024 passage of the pulsar through the circumstellar disk, we find the spectrum to be the most energetic (Γ = 1.5) around 27 days after periastron, during the first of two variable, short-term emission episodes of a contemporaneous GeV flare. We discuss the variability in the X-ray flux and the hardening of the spectrum with time, and in the context of previous observations and what that means for the competing energy loss and acceleration timescales.